FAKTOR-FAKTOR YANG MEMPENGARUHI PENGEMBANGAN KOMPETENSI GURU DI SMP NEGERI 46 PEKANBARU - Khoiruddin; Rizki Fadillah, Ade Irma (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2026)
This research aims to identify the factors that influence the development of teacher competency at SMP Negeri 46 Pekanbaru. Through a descriptive approach with interview and observation methods, this research explores various aspects related to pedagogical competence, challenges faced by teachers, and strategies applied in the learning process. Apart from that, this research also analyzes how internal and external factors, such as training, school management support, and the condition of infrastructure, contribute to the development of teacher competency. It is hoped that the research results will provide comprehensive insight into improving the quality of education in schools, as well as recommendations for developing educational policies that are more effective in supporting teacher competency.